After 200 Years: The Structure of Bleach and Characterization of Hypohalite Ions by Single‐Crystal X‐Ray Diffraction. Issue 46 (20th August 2021) - Topić, Filip; Marrett, Joseph M.; Borchers, Tristan H.; Titi, Hatem M.; Barrett, Christopher J.; Friščić, Tomislav
Abstract: We report the first X‐ray single crystal structures of hypochlorite (ClO − ) and hypobromite (BrO − ) salts, including hydrated sodium hypochlorite, a staple of the chlorine industry and ubiquitous bleaching and disinfection agent for almost 200 years. The structures, supported by variable‐temperature Raman spectroscopy on individual crystals and periodic density‐functional theory (DFT) calculations, provide insight into solid‐state geometry and supramolecular chemistry of hypohalite ions. Abstract : We fill a gap in fundamental and applied chemistry by providing the first X‐ray single crystal structure characterization of hypohalite ions, including sodium hypochlorite: the active component of liquid bleach, in use as a bleaching agent and sanitizer for at least two centuries.